Effects of Brucea javanica and Piper betle extracts on oral Candida SPP / Mohd-Al-Faisal Nordin - Mohd Al-Faisal, Nordin (2012)
Candida species is an opportunistic microorganism residing in the human oral cavity. There is increasing prevalence of candidal infections in the oral cavity largely because of the increasing size of the population at risk. The rise in diagnosed cases of oral candidiasis is also due to the immunosuppressive effect of prescribed antifungal agents on resistant hosts. The ability of Candida species to adhere on mucosal tissues and/or denture surfaces, and the production of hydrolytic enzymes along with defective host immunity are among the known key factors of invasions and pathogenesis of oral candida. Although Candida albicans remains as the most pathogenic organism, the emergence of non-Candida albicans Candida (NCAC) species with reduced susceptibility to prescribed antifungal agents has prompted efforts to study antifungal agents from natural sources. Plants have long been known to possess medicinal values and are rich in chemical constituents that can be used in the development of antifungal products. Initially, seven local plants were systematically screened for their antifungal activity and two of them - Brucea javanica L. and Piper betle L. were selected based on their positive antifungal activities on seven Candida species tested. The specific objectives of this study were; (i) to determine the minimum inhibition concentration (MIC) and minimum fungicidal concentration (MFC) values of the extracts, (ii) to investigate the growth inhibitory effect of the extracts based on changes in the pattern of growth profile of each Candida species, (iii) to investigate the influence of extracts on adherence mechanisms which include the non-specific and specific bindings, (iv) to investigate any morphological changes of the cells following treatment with the extracts, and (v) to explore the differential expressions of multigene family of secreted aspartyl proteinases (SAPs) and hyphal cell wall protein 1 (HWP1).